2010
DOI: 10.1007/s00259-010-1406-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging in atherosclerosis

Abstract: Atherosclerosis is the major cause of cardiovascular disease, which still has the leading position in morbidity and mortality in the Western world. Many risk factors and pathobiological processes are acting together in the development of atherosclerosis. This leads to different remodelling stages (positive and negative) which are both associated with plaque physiology and clinical presentation. The different remodelling stages of atherosclerosis are explained with their clinical relevance. Recent advances in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 145 publications
(159 reference statements)
1
12
0
1
Order By: Relevance
“…For years it has been tried to image coronary lesions by either single photon emission computed tomography (SPECT) or PET. Except for a few promising reports [20,21], attempts to visualize the vulnerable plaque have on the whole been disappointing due to a series of limiting factors [1,2,22]. However, with the idea of measuring global molecular cardiovascular calcification conceptually years, perhaps decades, before it becomes macroscopically visible, things may change dramatically.…”
Section: Right Upper Panelmentioning
confidence: 99%
See 3 more Smart Citations
“…For years it has been tried to image coronary lesions by either single photon emission computed tomography (SPECT) or PET. Except for a few promising reports [20,21], attempts to visualize the vulnerable plaque have on the whole been disappointing due to a series of limiting factors [1,2,22]. However, with the idea of measuring global molecular cardiovascular calcification conceptually years, perhaps decades, before it becomes macroscopically visible, things may change dramatically.…”
Section: Right Upper Panelmentioning
confidence: 99%
“…Functional imaging critically looking into each of these distinctive processes can provide insight into their formation, progression, vulnerability, and resulting atherothrombotic complications. The concept of the vulnerable coronary plaque, i.e., the soft, lipid-filled endothelial swelling with a fibrous cap that may disrupt and cause a cascade of thromboembolic processes leading to occlusion and acute myocardial infarction more often than narrow calcified stenoses, has led to a search for methods that can detect these culprit lesions in the coronary bed [2,17]. Further, it has served as a basis for the creation of a novel practice guideline for cardiovascular screening in the asymptomatic at-risk population.…”
Section: Right Upper Panelmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, currently there is not a specific tracer that can be used as a diagnostic tool to diagnose prospective AMI/ACS in patients. 18 It was a valuable discovery when acute plaque rupture was found to be the major cause of sudden coronary death. 20 From the examination of more than 800 cases of sudden coronary death at autopsy, Finn et al found that 55-60% of subjects had underlying plaque rupture as the etiology.…”
Section: Vulnerable Plaques and In Vivo Detectionmentioning
confidence: 99%